Process of sanitation of certified free properties of brucellosis and tuberculosis in the State of São Paulo - Carraro, Paulo Eduardo [UNESP]; Bürger, Karina Paes [UNESP] (My University, 2019)
The aim of this study was to analyze the sanitation process of the properties certified as free of brucellosis and tuberculosis in the State of São Paulo. However, 14 properties with free certification, between the years 2001 and 2016, were identified and analyzed. The municipalities of the properties were geoprocessed on the map of the state livestock circuit. Through descriptive statistics, a semi-structured questionnaire was evaluated with questions related to the profile of properties (characteristics of the owner, property, production and questions related to human, animal and environmental health) and to the sanitation process. The results showed that, in the state of São Paulo, the 14 certified properties free of brucellosis and tuberculosis were not uniformly distributed, it had herds with 90 to 500 animals, monthly veterinary assistance and milk production was technified with medium or large production capacity milk daily. The owners had an average age of 63, 92.8% (13/14) of them with a higher education level and found difficulties to obtain and maintain the certificate. These properties, even in the process of sanitation, had reinfection in the herd, evidencing the complexity in combating the diseases and the need for more joint actions among the whole community.
Keywords: Control; Eradication; Health program; Milk; Zoonosis